Adaptive invention: independence and mobility through modifications. (3rd October 2018) - Mairami, Fatima Fanna; Allotey, Pascale; Warren, Narelle; Mak, Jun Shin; Reidpath, Daniel Diamond
Abstract: Background: Stroke is a leading cause of disability that limits everyday activities and reduces social participation. Provision of assistive devices helps to achieve independence and social inclusion. However, due to limited resources or a lack of suited objects for their needs, individuals with disabilities in low and middle income countries (LMIC) often do not have access to assistive devices. This has resulted in the creation of purpose built innovative solutions. Methodology and case content: This paper uses a single case derived from a larger ethnographic study of stroke survivors in rural Malaysia to demonstrate the role of assistive devices in shaping stroke recovery and how existing structures can be modified. Second, the concept of affordances in relation to structures within the environment, issues of affordability and accessibility of assistive devices for individuals in LMIC are discussed. Findings and conclusions: Stroke recovery involves adapting to new limitations and discovering the support necessary to live life. These changes are influenced by a range of environmental factors. Healthcare professionals need to support stroke patients in identifying challenges and work to find innovative ways to address them. Stroke survivors may benefit from the use of an assistive device beyond its clinical function to participate purposefully in activities of daily living. Implications for Rehabilitation: Stroke is a cause of disability that limits everyday activities and reduces social participation. Assistive devices help achieve independence, social inclusion and shape stroke recovery. Individuals with disabilities in low and middle income countries often do not have access to assistive devices and resort to innovative solutions that are purpose built. Stroke recovery involves adapting to new limitations and discovering the support necessary to live life as best as possible.